IMPLEMENTASI TERHADAP PERATURAN BANK INDONESIA NOMOR 18/16/PBI/2016 TENTANG RASIO LOAN TO VALUE UNTUK KREDIT PROPERTI DAN RASIO FINANCING TO VALUE UNTUK PEMBIAYAAN PROPERTI - Ismi, Hayatul; Fitriani, Riska; ', Angelina (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2018)
Number of population growth in a city then the more shelter house emerged. As of shelter in the wake up with themselves, housing, and also the house of rows (apartments). Shelters are built with their own previously must have flat land first before starting to build a building remains. This time to get the land broad and strategic location in the City of Pekanbaru is more difficult in the add again the price of the land that is becoming more and more days increasing cause some more choose shelter directly so as of housing (apartments) and housing.Developer currently compete to build a shelter answered the question the community in selecting shelter.Many interesting offers that are provided by the developer in the form of advertising flyers and brochures so that people can see and are interested to have a house in want with DP and low interest rate installment also 0%. The Ad in the form of the offer for sales service distribution and properties of anything to exist or not exist, real, personal or mixed, or other goods that can affect people - people either directly or indirectly.This type of research can be categorized in types of sociological research, because in this study the author used how to interview, find sample is also the literature of the materials such as the official documents, books to do research in this study, data sources used, main data, data secondary and tertiary data , the technique of data collection in this study by the methods an overview of the library or field study.The implementation of Bank Indonesia Regulation No. 18/16/PBI/2016 about the ratio of Loan To Value for property credit and Financing to value for the financing of the property is not running well in the city of Pekanbaru, because there are several factors that affect to apply the regulation, some factors was from the bank, consumers and does not expressly sanction given.Suggestion of author, Firstly, The Bank Indonesia should be more decisively against Banks vie shari'a in Pekanbaru, Second, sharia banks should reject customers who want to do the mortgage financing that more than 85%, And the last developer should not do sales system pre-project selling because it is very risky, also sock away more should be more carefully and learn their personal finances.Keywords: Credit Shari'a - The Financing of the Property